Caries rate in children aged 6 to 12 in the "agua dulce and lago victoria" educational units in the municipality of Puerto Gonzalo Moreno-Bolívia (Research, Society and Development, 2024)
An epidemiological survey of oral health in children makes it possible to plan, implement health actions and monitor disease behaviors, since caries is a type of persistent imbalance that occurs in both developed and developing countries. The aim of this study was to identify the caries rate in children aged 6 to 12, using the ceo-d and CPO-D epidemiological indices, in two educational units in “Agua Dulce and Lago Victoria”, in the municipality of Puerto Gonzalo Moreno, Bolivia. The methodology used corresponds to a descriptive epidemiological study of two caries indices in children, by means of observation and identification research, the sample was made up of students aged between 6 and 12 years, in two educational units of “Agua Dulce and Lago Victoria”, located in the municipality of Puerto Gonzalo Moreno in Bolivia. The results showed that the DMFT index was 6.7 and the DMFT was 2.3 in the two educational units, and that male children had a DMFT of 2.1 and female children had a DMFT of 2.7. Although they provide data on the prevalence of caries, they do not directly address the underlying causes, such as socioeconomic or behavioral factors. In conclusion, there is a high rate of caries in boys and girls in both communities, which is due to the lack of knowledge about oral hygiene in families, as well as the lack of financial resources to buy toothbrushes and toothpastes for their children.